POLIMORFISME GEN YANG MENYANDI KAPPA KASEIN PROTEIN SUSU PADA SAPI PERAH - , YOSI ANDIKO ANGGARKUSUMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kappa casein (Îº-casein) gene is one of the milk proteins that can be used to determine the quality of dairy animals. Î-casein genes make up about 15% of the casein fraction of milk of dairy cows. To date there are nine known variant alleles (A, B, C, E, F, G, H, I and A1) of the Îº-casein gene. Variant alleles A and B are the most common variant allele dominates in most cattle breeds. Kappa casein B variant was reported favorably to the quality of milk and is considered to be included in a dairy animal breeding strategies. Research with the aim of identifying the Îº-casein genotype and associated with quality milk from dairy cows in farms Baturaden KP4 Yogyakarta and Central Java. The number of dairy cows used in this study was 23 tail, consisting of as many as 14 dairy cows KP4 tails, and tails of dairy cattle Baturaden 9. At the stage of research include blood sampling, DNA extraction, DNA amplification using PCR with primers consisting of two kinds, namely forward and rivers: K1 (5'-GTC CAC CAC ACC ACC ATT CAC TATC-3') and K2 (5'-GCC CAT TTA TAA-3'). Results of Îº-casein gene PCR and analyzed by RFLP enzymes Hinf I and Hind III. The results of research after ristriksi digested using Hinf I enzyme gene polymorphisms of DNA obtained Îº-casein milk with each allele having a molecular weight of 90-270 bp. While genes are digested using the enzyme Hind III ristriksi describe the absence of undigested allele.